Sistem Pendukung Keputusan Penerimaan KIP Menggunakan Metode Multi-Objective Optimization by Ratio Analysis (MOORA) - Eka Gustina Bancin; Ebenezer Bangun; Muhammad Syahrizal; Hetty Rohayani (ADA Research Center, 2025)
The Indonesia Smart Card for Higher Education (KIP Kuliah) is a government-funded scholarship program designed for students with strong academic potential but limited economic resources, as regulated in Minister of Education and Culture Regulation No. 12 of 2015 on the Indonesia Smart Program. Universitas Budi Darma Medan is one of the universities entrusted to accept and select prospective scholarship recipients. However, the large number of applicants requires a decision support system (DSS) to make the selection process more objective, efficient, and accurate. This study applies the Multi-Objective Optimization by Ratio Analysis (MOORA) method to determine KIP recipients. The MOORA method was chosen for its simplicity, flexibility, and effectiveness in weighting and ranking alternatives based on several predetermined criteria, namely number of achievement certificates, parents’ income, interview test scores, written test scores, and home ownership. Data from seven applicants were analyzed using weights established by the university. The results show that MOORA successfully generated a clear and measurable ranking, with alternative A5, Fredy Fau, obtaining the highest score of 0.1725 and ranked first as the best candidate for KIP assistance. Therefore, the application of the MOORA method within a DSS proves effective in assisting universities to carry out the selection process objectively and transparently.